OPTIMASI PROSES PENETRALAN AIR ASAM TAMBANG PADA SETTLING POND PT DARMA HENWA TBK JOBSITE PT ARUTMIN INDONESIA SITE ASAM-ASAM - Maulana, Tri Okta; Mirwan, Agus; Heryani, Hesty; Mizwar, Andy (Universitas Lambung Mangkurat, 2023)
One of method which ussualy used in neutralizing Acid Mine Drainage using neutralizing agents is Settling Pond. This treatment process requires adding neutralizing agents to the waters or through a mixing system and allowing deposits to form in the pond. Many factors and process mechanisms can affect the effluent quality of an Acid Mine Drainage processing system. The purpose of this study is to evaluate the effectiveness and optimize the Acid Mine Drainage neutralization process carried out in Settling Pond 19. The research method used is to make theoretical simulations both modeling using PHREEQC and calculations to simulate various neutralization process options. The results showed that the neutralization process was affected by the quality of the neutralizing agent, the number of doses, the saturation index (precipitation) limit, the dissolution process of the neutralizing agent, the duration of dosing, and the duration of neutralization. According to modeling and theoretical calculations, the technical recommendations for optimizing the Acid Mine Drainage neutralization process to produce effluent quality that meets wastewater quality standards are the duration interval to inject neutralizer from every 60 minutes to every 13.6 minutes with a continuous dosing mechanism; The use of a maximum dose of limestone of 0.22 g/L to avoid oversaturated events, and the use of a limestone dissolution mechanism before the injection process is carried out to reduce the need for retention time for 216 seconds.